2013
DOI: 10.1007/s11746-013-2266-4
|View full text |Cite
|
Sign up to set email alerts
|

A Chemometric Approach to Assess the Frying Stability of Cottonseed Oil Blends During Deep‐Frying Process: I. Polar and Polymeric Compound Analyses

Abstract: The main goal of the present study was (i) to determine the formation of degradation products in cottonseed oil (CSO) blends during deep frying process by adsorption and high performance size exclusion chromatography techniques and (ii) to evaluate the impacts of food additives on total polar (TPC) and polymeric compound (PTAG) formation using a chemometric approach. In order to prepare the frying CSO blends; ascorbic palmitate, mixed tocopherols, dimethylpolysiloxane, lecithin and sesame oils were used as add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
(36 reference statements)
0
14
0
Order By: Relevance
“…[16, 22,23] To the best of the researcher's knowledge, no study has been reported on blending of palm olein oil (POO) with refined cottonseed oil (CSO) to formulate new frying oils, to modify pure/original oils to get better their physicochemical functionalities and to enhance their frying/oxidative stability. In the literature, there are some articles on the study of blending of palm, sunflower, corn, canola with other refined or cold-pressed edible oils, seed oils, food additives or others.…”
Section: International Journal Of Food Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[16, 22,23] To the best of the researcher's knowledge, no study has been reported on blending of palm olein oil (POO) with refined cottonseed oil (CSO) to formulate new frying oils, to modify pure/original oils to get better their physicochemical functionalities and to enhance their frying/oxidative stability. In the literature, there are some articles on the study of blending of palm, sunflower, corn, canola with other refined or cold-pressed edible oils, seed oils, food additives or others.…”
Section: International Journal Of Food Propertiesmentioning
confidence: 99%
“…These values range from 23% to 29% for the TPC and 12% to 15% for total polymerized lipids. [22,32] Therefore, in this research the changes of TPC and polymeric compound contents for pure and blend oils, were determined by using IUPAC column chromatography method and HPSEC/ ELSD techniques, respectively. The contents of TPC in pure and blend oils were increased linearly with frying time ( Table 2).…”
Section: International Journal Of Food Propertiesmentioning
confidence: 99%
“…Frying procedure was performed according to our previous study. [21] The samples were stored in a refrigerator in brown glass-stoppered flasks to avoid further chemical changes and filtered with 0.45 µm pore size filter before chromatographic analyses.…”
Section: Frying Proceduresmentioning
confidence: 99%
“…Therefore, these natural antioxidants are retained at high levels in fried products and responsible for longer shelf life of products. [15][16][17][18]21] In order to improve stability of frying oils; emulsifiers, natural & synthetic antioxidants, antipolymerizing, anti-spattering and anti-foaming agents have been used to protect them from oxidation. Commercially rapeseed, sunflower, corn, palm and hydrogenated vegetable oils are chosen for frying applications.…”
Section: Introductionmentioning
confidence: 99%
“…Hydroperoxides are decomposed into other species more oxidized as aldehydes, ketones and organic acids, which by successive reactions form highly oxidized compounds. The concentration of all this species can be measured over time and are called Polar Compounds Total (CPT), which are indicators of the final oil deterioration (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%